Characterization and enantiomer separation of indene-derived hexacyclic hydrocarbon and its application as a chiral source. (7th May 2021) - Kodama, Koichi; Yamaguchi, Shohei; Hayano, Shigetaka; Houkawa, Takashi; Kitahara, Yoshinori; Shitara, Hiroaki; Hirose, Takuji
Abstract: A hexacyclic chiral aromatic hydrocarbon (1 ), obtained by the reaction between indene and cyclopentadiene, has been characterized, and its enantioseparation has been achieved by the combination of stereoselective complexation with β-cyclodextrin and recrystallization. This method has been applied in the large-scale production of both pure enantiomers of 1 . Enantiopure 1 and its derivatives have been used as chiral dopants in nematic liquid crystals. Graphical abstract: Image 1 Highlights: Characterization of a rigid hexacyclic chiral hydrocarbon with conglomerate nature. Enantiomer separation by selective complexation with β-cyclodextrin and recrystallization. Application of its derivatives as chiral dopants for nematic liquid crystals.